Optimizing Slimmable Networks for Multiple Target Platforms - Wang, Zifu; Blaschko, Matthew (Proceedings of the Northern Lights Deep Learning Workshop, 2022)
In this work, we extend platform-aware adaptive training to the weighted average of multiple target platforms, where the weighting is determined e.g. by the market share of the target platform. To simulate different market regimes, we generate different weight settings by a Chinese restaurant process to benchmark optimization strategies. We use a neural architecture search framework based on Markov Random Fields to efficiently find the optimal channel configurations for each platform, and investigate different sampling strategies to train a single slimmable network that can be deployed to multiple platforms at the same time. Empirical results on CIFAR-100 demonstrate improved performance over the original slimmable network across different weight settings, while maintaining efficient training.